Investigation of Thermodynamic Properties of Ni30Ti50Cu20 Shape Memory Alloy - Ercan, Ercan; Dagdelen, Fethi; Kök, Mediha; Balci, Esra (My University, 2019)
In this study, after producing Ni30Ti50Cu20 shape memory alloy by using arc melting technique, some examinationwas performed, including phase transformation temperatures, microstructural features, and certain thermodynamicparameters. The DSC thermogram run with 10°C/min heating-cooling rate, and thus it was determined thataustenite start (As) temperature is 23.5 oC, austenite finish (Af) temperature is 50.6 oC, martensite start (Ms)temperature is 26.7 oC and martensite finish (Mf) temperature is -0.10 oC. For different heating rate of DSCmeasurements, it was observed that martensite to austenite phase transformation temperatures (As and Af) arechanged, while it did not effect on the reversible martensite phase transformation temperature (Ms and Mf). Thermalactivation energy of the alloy was measured by Kissinger method, which is Ea=63.208 kJ/mol. Moreover, Gibbsfree energy was slightly increased with increasing heating-cooling rates. The DSC curves and XRD crystal analysisshowed the phase transformation was occurred in a single step B2 ?B19. Beside, some precipitations like Ti2(Ni,Cu) as well as matricesin the form of TiNi0.8Cu0.2 of element Cu dissolved in interphases of NiTi were encountered.SEM-EDX was used to determine chemical composition of Ti2(Ni, Cu) phase in atomic percentage (at.%). Themicrohardness of the alloy was 219 HV, where Cu element was added to makes alloy to be softer than thetraditional binary NiTi alloys.
Keywords: Nanobilim ve Nanoteknoloji; Termodinamik; Malzeme Bilimleri; Özellik ve Test